Evaluating the efficacy of dried distillers grains with solubles as a replacement for soybean meal in a Boer goat diet - Rimmer, Linnea A.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
Goat meat is in high demand worldwide, even if the United States domestic consumption is relatively low. This makes goat nutrition and diet cost an important area of study. With the per protein unit cost discount of dried distiller grains with solubles (DDGS) over soybean meal (SBM) being $1.86, it may be more economical to incorporate into goat diets. Unfortunately, there is limited data on the equivalent nutritional value for goat producers that would encourage them to use DDGS in replacement of SBM. Therefore, the objective of this experiment was to evaluate the efficacy of DDGS as a replacement for SBM in a Boer goat diet. The experiment used forty-eight randomly assigned Boer goat kids (approximately 70 d of age and initially 28.2 kg). The goats were penned in groups of three, and fed in a titration design with four treatments: 0%, 33%, 66%, and 100% SBM replaced by DDGS, with four replicates per treatment. The feed was pelleted, with the pellets containing roughage, so no additional roughage was needed. An initial average goat weight was established after a fourteen-day step-up period and thereafter weights were recorded weekly to determine ADG, ADFI, G:F. At the end of the 47-day experiment, two goats from each pen were slaughtered in a USDA-inspected facility. Carcass weight, carcass yield, loin eye area, loin eye depth, backfat depth and body wall thickness were recorded. Data was analyzed using the GLIMMIX procedure of SAS (SAS Inst., Cary, NC) with pen as the experimental unit and the alpha value being ≤ 0.05. Dietary treatment impacted (P<0.001) overall G:F, but did not impact ADG, ADFI (P>0.10). This was driven by the linear improvement (P<0.02) in overall ADG and G:F with increasing DDGS, and the significant increase in body weight during d 21 to d 28. Overall, the greatest (P<0.05) feed efficiency was seen in goats fed either 66% or 100% of SBM replaced by DDGS. There was no significant difference (P>0.10) in the carcass data collected. This experimental data demonstrates that DDGS can be used in replacement of SBM in meat Boer goat diets.
Keywords: Spring 2018